Interpretation of angular momentum of the leg segment in Dwihoolyu-chagi of Taekwondo - Lee, S. H.; Lee, D. (1999)
Chagi motion of Taekwondo is executed by the complex movements of the leg muscle such as flexion and extension around the knee joint. The rotational movement of the body can be interpreted in terms of the change in angular momentum. However, the calculation of angular momentum using the classical cinematography is not easy because the inertia tensor in the global reference system change every frame. Also, the markers should be attached to the subject to measure the rotational factors. The purpose of this study was to extract the equations of motion for the inertia tensors and angular momentum using the transformation method of coordinate axis. A Korean representative athlete in Taekwondo was employed to verify the theoretical approach. Two high speed camera was used to film the motion of the subject and the speed was set at 100fps. The dominant leg was used to do Dwihoolyu-chagi. DLT method was employed to get the spatial coordinates of body segment and Kwon3D software was used to process the data collected. To compute the tri-axis moment of inertia in the leg, Zatsiorsky`s scaling factor was applied. There were four events, i.e., starting(RD), take-off(TO), minimum knee angle(MKA), and impact(IMP), and three phases, preparation, flexion, and extension in chagi motion. There exists the displacement vector () of the leg in global reference system and rotational direction of moment of inertia() in local reference system. The direction of axis in local reference is , subscript t denotes the thigh, s denotes shank, and f denotes foot. The direction of the leg was set from the anatomical position, lateral 1, frontal 2, axis 3 which connect the proximal to distal of the segments.